Evaluation of uveitis activity in Behcet's disease patients using BOS24 - V. V. Neroev; G. A. Davydova; L. A. Katargina; T. A. Lisitsyna; Z. S. Alekberova; Z. R. Khatagova (Российский офтальмологический журнал, 2018)
Purpose: to estimate the change of uveitis activity using Behcet’s disease ocular attack score 24 (BOS24) during anti-inflammatory and immunosuppressive therapy of Behcet's disease (BD) patients. Material and methods. 144 out of 205 patients (70.2 %) with confirmed BD diagnosis (according to the criteria set out in ISGBD, 1990) had ocular lesions, 83 of 144 (57.6 %) had acute uveitis, 145 eyes displayed active inflammation. Uveitis activity was estimated in dynamics using BOS24 score, which consisted of 6 parameters with the maximum level of 24 points. Results. The initial average BOS24 score for 145 eyes with active uveitis was 7.38 ± 0.71 points. The most pronounced inflammatory changes were revealed in posterior pole areas - mostly in retina periphery, less frequently in the area of fovea and the optic disc. All patients with uveitis exacerbation received systemic therapy including glucocorticoids, cyclosporine and/or azathioprine. After 9.43 ± 2.47 months of therapy, the average BOS24 score dropped significantly (р < 0.001) to 1.86 ± 0.48. The most notable positive changes were revealed in the anterior chamber (р < 0.001), the vitreous (р = 0.002) and in retinal periphery (р < 0.001). Conclusion. BOS24 is a reliable tool allowing a quantitative assessment of uveitis activity in BD patients and its change after anti-inflammatory and immunosuppressive therapy. For citations: Neroev V.V., Davydova G.A., Katargina L.A., Lisitsyna T.A., Khatagova Z.R., Alekberova Z.S. Evaluation of uveitis activity in Behcet's disease patients using BOS24. Russian ophthalmological journal. 2017; 10 (4): 30-7. doi: 10.21516/2072-0076-2017-10-4-30-37 (In Russian).